Ceroscopa sojina : produção de esporos, densidade de inóculo de reação de cultivares de soja - Gomez, Diana Érica (2011)
The frogeye leaf spot caused by the fungus Cercospora sojina Hara reduces foliar photosynthetic area by necrotic ilesions and/or precocious defoliation in the soybean crop [Glycine max (L.) Merril]. In Argentine the information on the present races and the grade of resistance of some local varieties is limited. Disease caused epidemic in the 2008/2009 and 2009/2010 growing seasons. It caused intense damage in the provinces of Cordoba and Santa Fe in genotypes of short and intermediate cycles. Because the pathogens are disseminated by seeds to long distances, it is considered necessary to evaluate the resistance grade of cultivars. The objectives of this study were: to characterize morphologically the causal agent, to evaluate the effect of different substrates in the sporulation, presence of light and the dark, pH and osmotic potential. The temperature effect, pH and osmotic potential in the germination of conidia were quantified. Effect of different inoculum densities and adjuvant use on the number and diameter of lesions were also studied. Finally the reaction of soybean cultivars to the pathogen was evaluated. This work was conducted in the Laboratory of Phytopathology of the Faculty of Agronomy and Veterinary Medicine of the University of Passo Fundo and Laboratory Regional of Vegetal Pathology to Farming Experimental Station (EEA) INTA Sáenz Peña, Chaco, Argentine. By the pathogenicity test, fungus morphologic characterization and by the comparison with